Pengembangan Bahan Ajar LKPD (Lembar Kerja Peserta Didik) Biologi Sains Berbasis Pendekatan Inquiry Terbimbing Pada Sub Pokok Bahasan Fotosintesis - Nursafiah Nursafiah (Universitas Islam Sumatera Utara, 2020)
Based on an observation done at Senior High School 1 Badar, the most common problems found was on student worksheets (LKPD) used in the learning process which only in the form of question sheets so that they only focused on verbalism skills. Based on this issue, the researcher want to develop the students worksheet (LKPD) and find out the appropriateness of the development in student worksheet based on guided inquiry. This is researh and development (R D), which is a method used to produce a particular product by testing the effectiveness of the product. Validation of material experts on the content feasibility component shows the total score of 194 with a percentage of 88 .18%, with the